Impact of Strategic Planning on the Performance of Yemeni Universities - Abdullatif Musleh Mohammed Ayedh; Omer Hasan Mohammed Omar (University of Science and Technology, Yemen, 2020)
This study aimed to investigate the impact of three strategic planning dimensions (environmental analysis, strategic direction and strategy formulation) on the five performance dimensions of Yemeni universities (profitability, market share, social responsibility, customer satisfaction, and scientific research). The descriptive analytical method was used and the data were collected by using a questionnaire. The study population consisted of the academic and administrative leaders in the Yemeni universities from which a sample of 301 participants were selected using the census method. To achieve the study objective and test the hypothesis, the descriptive and inferential statistical methods were used. The results of the study revealed an interest in practicing strategic planning dimensions in the Yemeni universities under investigation. There was a disparity in the level of achieving the performance dimensions, where 'market share' was the most achieved dimension, and 'profitability' was the least achieved dimension. The results also showed a disparity in the impact of strategic planning dimensions on the performance of Yemeni universities, where 'strategy formulation' was the most influential dimension; and 'strategic direction' was the least influential dimension. It was concluded that Yemeni universities should direct more focus on their practice of strategic planning of all dimensions because it has a positive impact on their performance. Keywords: strategic planning, performance, Yemeni universities